REPRESENTASI PERAN IBU DALAM IKLAN (ANALISIS SEMIOTIKA PADA IKLAN BERTEMA HARI IBU) - Mudafiuddin, Birda (Jurnal Common, 2020)
Advertising is a complex communication pattern that moves towards goals and uses strategies that influence the thoughts, feelings, and behavior of consumers. This study aims to describe the meaning of the Role of Mother contained in YouTube advertisements in December 2017 with the theme "Mother's Day". The research method used is descriptive-qualitative data analysis techniques using the semiotic analysis of Roland Barthes using the terms denotation, connotation and myth to find out the meaning of the values ​​of the mother's role in the ad. Whether the results of the analysis of this study are indicative of the understanding of motherism in advertisements conducted by researchers. This understanding of motherism is marked by symbols of Mother's role as educators, sources of affection and a person who supports double. Keywords : Mother's Role, Representation, Motherism and YouTube Advertising.